Multivariate analysis of regional variations in quality, safety, and flavor of commercial fragrant rapeseed oils in China - Yu Li; Baijun Chu; Shu Wang; Wu Zhong; Jiaojiao Yin; Pan Gao (Food Chemistry: X, 2025)
This study analyzed commercial fragrant rapeseed oils (CFROs) from the Southwestern aera, the Central area, the Eastern area, and the Northwestern area in China. Headspace solid-phase microextraction (HS-SPME)-gas chromatography–mass spectrometry (GC–MS) coupled with quantitative descriptive sensory analysis was used to assess quality indicators covering physicochemical properties, nutrients, safety parameters and volatile compounds. The aim was to provide scientific support for determining the geographic relevance of the quality of FCROs products for regional production optimization, safety improvement and consumer guidance. Results showed that CFROs from the Southwestern area had higher acid values (0.80 mg/g) and tocopherol (525.6–618.5 mg/kg). Fatty acids showed no significant regional differences, but the Southwestern and Eastern areas have higher monounsaturated levels. Sensory evaluation revealed the Southwestern area CFROs scored highest for nutty/roasted flavor (average: 3.9) and spicy flavor (average: 4.2). A total of 97 volatile compounds were identified, the Southwestern area had higher concentrations of 2-ethyl-5-methylpyrazine, which imparted nutty/roasted flavors, and glucosinolate degradation products (1-butene-4-isothiocyanate) that contributed to spicy flavors. Oxidation products (aldehydes, ketones) linked to grassy and oily flavors were also highest in the Southwestern area. Principal component analysis indicated CFROs from the Southwestern area had the best quality. These findings provide valuable insights for CFRO production and consumer choice.